Pengaruh Disiplin Kerja dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Teluk Luas Padang - Anisa Sintya Melani; M. Afuan; Nila Pratiwi (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine the effect of work discipline and leadership style on employee performance through job satisfaction as an intervening variable at PT Teluk Luas Padang. The study population was 66 employees at PT Teluk Luas Padang. The sampling technique used was a saturated sampling method with a sample of 66 employees. Data collection was conducted through a questionnaire that had been tested for validity and reliability. The data analysis technique used the Structural Equation Modeling (SEM) SmartPLS 3 method. The results of the study at PT Teluk Luas Padang indicate that work discipline significantly influences job satisfaction. Leadership style significantly influences job satisfaction. Work discipline does not significantly influence employee performance. Leadership does not significantly influence employee performance. Job satisfaction significantly influences employee performance. Work discipline significantly influences employee performance through job satisfaction. Leadership style significantly influences performance through job satisfaction.